Happiness and depression in adolescence after maternal smoking during pregnancy: birth cohort study. - Ana Maria Baptista Menezes; Joseph Murray; Mitzi László; Fernando C Wehrmeister; Pedro C Hallal; Helen Gonçalves; Maria Cecilia F Assunção; Carolina Baptista Menezes; Fernando C Barros (PLoS ONE)
Background Prenatal cigarette smoke exposure may have adverse psychological effects on offspring. The objective was to assess the association between parental smoking during pregnancy and offspring happiness at age 18, as well as depression. Methodology Participants were part of a birth cohort study in Pelotas, Brazil (5,249 participants). Happiness was measured by the Subjective Happiness Scale, a Likert-like scale with four questions generating a score from 1 to 7, with ≥ 6 indicating "happiness". Depression was measured using the Mini International Psychiatric Interview. Results About one third of mothers reported having smoked during pregnancy and 4.6% reported smoking 20 or more cigarettes a day. The prevalence of happiness was 32.2% (95% CI 30.8; 33.7), depression 6.8% (95% CI 6.1; 7.6), and simultaneous happiness and depression less than 1%. The prevalence of offspring happiness decreased as smoking in pregnancy increased, even after control for confounding variables, showing an OR = 0.79 [95% CI 0.55; 1.13]. The opposite happened to depression; the prevalence of offspring depression increased as smoking in pregnancy increased (<20 cigarettes/day OR = 1.38 [95% CI 1.03; 1.84] and ≥ 20 cigarettes/day OR = 2.11[95% CI 1.31; 3.40]. Smoking by the partner was associated with decreased offspring happiness after adjustment for confounders, but did no show association with offspring depression. Conclusions Offspring were less likely to be happy and more likely to be depressed if their mother smoked during pregnancy, and less likely to be happy if their father smoked during mother's pregnancy. Although we can not affirm that this is a "causal pathway", public policies to reduce smoking in pregnancy could improve the health of the offspring in the short and long term.